STRATEGI KREDIT MACET “PANG PADE PAYU” PADA LEMBAGA PERKREDITAN DESA DI KABUPATEN BULELENG - Ni Made Sri Ayuni; Ni Wayan Novi Budiasni (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2019)
ABSTRACTThis research is motivated by the phenomenon in the district of Buleleng related to the number of LPDs with unhealthy conditions until jammed have increased. In addition, the number of LPDs that have jammed in Buleleng Regency has the highest number in Bali. The purpose of this study is to know the implications of the internal control system and credit policy on credit settlement strategies, the disruption of bad credit is solved by the principle of "Pang Pade Payu". The numbers of samples in this study were 60 LPDs which were selected based on the stratified random sampling method. The data analysis technique used in this study is a structural equation model (structural equation modeling-sem) based on variance or component based sem with a smartpls 3.0 analysis tool. Based on the results of testing the internal control system has a significant positive effect on the strategy of resolving bad credit Bad Credit Strategy "Pang Pade Payu" at the LPD in Buleleng Regency. Both credit policies have a significant positive effect on the strategy of resolving bad credit Bad Credit Strategy "Pang Pade Payu" in the Village Credit Institution in Buleleng Regency.Keywords: Internal Control System, Credit Policy and Bad Credit Strategy, Settlement StrategyABSTRAKPenelitian ini dilatarbelakangi oleh fenomena di kabupaten buleleng terkait jumlah LPD dengan kondisi yang kurang sehat hingga macet mengalami peningkatan. Selain itu, jumlah LPD yang macet di kabupaten Buleleng menjadi jumlah terbanyak di Bali. Tujuan penelitian ini ialah mengetahui implikasi sistem pengendalian internal dan kebijakan kredit terhadap strategi penyelesaian kredit, penyeselaian kredit macet diselesaikan dengan prinsip “Pang Pada Payu”. Jumlah sampel pada penelitian ini adalah 60 LPD yang dipilih berdasarkan metode stratified random sampling. Teknik analisis data yang digunakan dalam penelitian ini adalah model persamaan struktural (structural equation modeling-sem) berbasis variance atau component based sem dengan alat analisis smartpls 3.0. Berdasarkan hasil pengujian sistem pengendalian internal berpengaruh positif signifikan terhadap strategi penyelesaian kredit macet Strategi Kredit Macet “Pang Pade Payu” Pada LPD Di Kabupaten Buleleng. Kedua kebijakan kredit berpengaruh positif signifikan terhadap strategi penyelesaian kredit macet Strategi Kredit Macet “Pang Pade Payu” Pada Lembaga Perkreditan Desa Di Kabupaten Buleleng.Kata kunci: Sistem Pengendalian Internal, Kebijakan Kredit dan Strategi Penyelesaian Kredit Macet, Strategi Kredit Macet.